Down the Rabbit Hole: Interrogating Content Regulation of YouTube Kids Indonesia - Nurhaqiqi, Hanna (Universitas Semarang, 2024)
Introduction: Given the rapid development of the digital media industry, it is essential to recognise the importance of YouTube, a widely used platform. In 2015, YouTube launched YouTube Kids, a platform designed specifically for children to provide content appropriate for young audiences. Methods: This research uses a qualitative method by focusing on YouTube channels with children as the leading content creators, namely on @leikagarudita accounts, @AishwaNahlaOfficial, @abilfatankey, and @ArinagaFamily with the theme of family and children. This study examines how the development of YouTube channels for children can provide space and new alternatives for a variety of content for adults on the YouTube platform and the content regulations governing their use. Based on the restriction rules given by YouTube Parental Control. What are the dynamics that arise in the use of YouTube Kids? Findings: The study revealed that content restrictions on YouTube Kids primarily target viewers under 13, based on information collection patterns on the YouTube Kids search page and Parental Access and Controls. Children are not given full access to account management at each stage, but parents or guardians have full authority over the YouTube Kids Company. The rules for using YouTube Kids are closely related to parental permission, aiming to provide content suitable for children. Originality: Although several studies have discussed the content of YouTube channels. However, no research has focused on family channel YouTube accounts focusing on children as the leading content creators.